FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PENETASAN ITIK (Anas domesticus) DI DESA KARANG TENGAH KECAMATAN BUAY MADANG TIMUR KABUPATEN OKU TIMUR (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2017)
Strategy priority that can be applied to develop the duck eggs hatchery (Anas domesticus) di Desa Karang Tengah Kecamatan Buay Madang Timur Kabupaten Ogan Komering Ulu Timur. Livestock-based agribusiness region development is one of program alternative that is expected to respond the challenges and demands of livestock development that is to improve the income and welfare of the community. Community needs for products of poultry farms is high enough that include eggs and bacon. Duck products include eggs and bacon were good comes from good breeders so eggs duck hatchery management and maintenance of ducklings or Day Old Duck (DOD) is needed. This study aims to determine the internal and external factors of duck eggs hatchery development, formulate alternative strategies and determine the priority of the Strategy priority that can be applied to develop the duck eggs hatchery (Anas domesticus) di Desa Karang Tengah Kecamatan Buay Madang Timur Kabupaten Ogan Komering Ulu Timur Regency. The research location is in Hamlet Krasak, Kagokan Village, Gatak District, Sukoharjo Regency. The data used are primary and secondary data. Data analysis used are regresi cobb douglas. The results showed production DOD doesn’t fulfill consumer demand yet. Internal and external factors affecting duck eggs hatchery. analysis used are regresi cobb douglas produced five alternative strategies, those are maintain and improve the quality of DOD based on the breeders experience with government guidance, defend the market with managing distribution system by government and miters assistance, increase the production of DOD to fulfill market demands with improving business management, cooperating with eggs suppliers in various areas for the supply and additional of raw materials continuously, and hold a breeders forum to share information on how to resolve the various problems about duck eggs hatchery. Strategy priority that can be applied to develop the duck eggs hatchery (Anas domesticus) di Desa Karang Tengah Kecamatan Buay Madang Timur Kabupaten Ogan Komering Ulu Timur.that is maintain and improve the quality of DOD based on the breeders experience with government guidance.